Challenges and Opportunities Facing the Chinese Economy in the New Decade: Epidemics, Food, Labor, E-Commerce, and Trade. Issue 6 (2nd November 2021) - Zhang, Yu Yvette; Zheng, Qiujie; Wang, Huashu
Abstract: As the rest of the world struggled to cope with the COVID-19 pandemic, China was the only major world economy to report growth in 2020. However, challenges still lie ahead. This special issue collects six articles that discuss the challenges and opportunities facing the Chinese Economy, addressing issues in food safety and regulation, the impact of COVID-19 on consumer and labor markets, and new opportunities in E-commerce and trade. These articles provide insights that can be useful for businesses and policy makers to navigate the impact of COVID-19, and draw implications that can last well into the new decade.